ANALISIS SENTIMEN PLATFORM YOUTUBE MENGENAI PRO KONTRA TERHADAP NATURALISASI PEMAIN SEPAKBOLA TIMNAS INDONESIA MENGGUNAKAN METODE NAÏVE BAYES - Vera Puteri Prasetyo (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
The naturalization of foreign football players into the Indonesian national team has sparked both support and criticism among the public, as reflected in YouTube comments. This study aims to analyze netizen sentiment using the Naïve Bayes algorithm. A total of 509 comments were collected and analyzed using RapidMiner. The best results were obtained from a single test with an accuracy of 72.55%, a precision of 83.58%, and a recall of 76.71%. Most comments were classified as positive toward naturalization, with 268 labeled as positive and 80 as negative. These findings demonstrate the effectiveness of the Naïve Bayes algorithm in classifying social media sentiment and indicate public support for the naturalization policy of football players.